Rapid, cost-effective and accurate quantification of Yucca schidigera Roezl. steroidal saponins using HPLC-ELSD method. (15th April 2017) - Tenon, Mathieu; Feuillère, Nicolas; Roller, Marc; Birtić, Simona
Graphical abstract: Highlights: Yucca steroidal saponins are widely used in food/feed industries. HPLC/ELSD is a new technique for measurement of Yucca steroidal saponins. Contrary to classical techniques, HPLC/ELSD is rapid, accurate and reliable method. HPLC/ELSD is a time- and cost-effective technique suitable for routine analyses. HPLC/ELSD can unravel plant adulteration issues. Abstract: Yucca GRAS-labelled saponins have been and are increasingly used in food/feed, pharmaceutical or cosmetic industries. Existing techniques presently used for Yucca steroidal saponin quantification remain either inaccurate and misleading or accurate but time consuming and cost prohibitive. The method reported here addresses all of the above challenges. HPLC/ELSD technique is an accurate and reliable method that yields results of appropriate repeatability and reproducibility. This method does not over- or under-estimate levels of steroidal saponins. HPLC/ELSD method does not require each and every pure standard of saponins, to quantify the group of steroidal saponins. The method is a time- and cost-effective technique that is suitable for routine industrial analyses. HPLC/ELSD methods yield a saponin fingerprints specific to the plant species. As the method is capable of distinguishing saponin profiles from taxonomically distant species, it can unravel plant adulteration issues.